Study on mesh stiffness and sensitivity analysis of planetary gear system considering the deformation effect of carrier and bearing. (May 2022) - Yang, Hongbo; Shi, Wenku; Guo, Lei; Zhao, Yanyan; Yuan, Renfei
Highlights: The meshing phase relationships between different gear pairs are calculated. The mesh stiffness considering flexibility of carrier and bearing is calculated by FE method. A mesh stiffness prediction method of planetary gear system is proposed and verified. Sensitivity analysis of effect of sun and ring crack on mesh stiffness is carried out. Abstract: The mesh stiffness characteristics and tooth root crack propagation of planetary gear system not only have an important impact on its transmission error, but further affect its vibration and noise level and the bearing capacity of gearbox. It is of great theoretical and engineering significance to study them comprehensively. First, the stiffness-damping model of the planetary gear mechanism is obtained by simplification, and the meshing phase relationships between the studied gear pairs are gotten by theoretical calculation. Then, through the FE modeling, the time-varying mesh stiffness of the sun-planet substructure, ring-planet substructure, and single-branch sun-planet-ring substructure are calculated respectively, and the influence of carrier and bearing flexibility on mesh stiffness is further studied. The mesh stiffness prediction method of the single-branch substructure is proposed and verified, and the overall mesh stiffness of the planetary gear system is predicted and analyzed. Finally, a sensitivity analysis model is established to study the effect of crack propagation at the root of sun and ring on mesh stiffness, capacity, and NVH features. The results show that the sun tooth root crack has a more significant impact on the mean stiffness and bearing capacity, and the ring tooth root crack has a more dramatic influence on the peak-to-peak stiffness and the vibration and noise characteristics of the gear system.